2020
DOI: 10.1177/1073191120911097
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Reports of Intimate Partner Violence Across Partners and Measures: The Impact of Posttraumatic Stress Disorder

Abstract: The Revised Conflict Tactics Scales (CTS2) is frequently used to assess intimate partner violence (IPV), but consistently yields low to moderate interpartner concordance of reports. Interpartner concordance on an alternative measure, the Event History Calendar Interview (EHCI), is largely unknown. We observed limited interpartner concordance of IPV reports on the CTS2 and EHCI, with wives generally reporting more IPV than husbands. Compared with the CTS2, the EHCI detected more cases of IPV, but not differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…We thus controlled for social desirability in analyses. As is typical (Marshall et al, 2020), couples generally had low levels of interpartner agreement in reports of IPV, which highlights the difficulties with obtaining accurate responses when assessing aggression via self-reports retrospectively. To address these limitations, researchers are recommended to develop multimodal methods of assessment.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…We thus controlled for social desirability in analyses. As is typical (Marshall et al, 2020), couples generally had low levels of interpartner agreement in reports of IPV, which highlights the difficulties with obtaining accurate responses when assessing aggression via self-reports retrospectively. To address these limitations, researchers are recommended to develop multimodal methods of assessment.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%
“…The current research had strengths and limitations. In the first place, the use of couples as a unit of analysis allowed us to address some limitations that have been pointed out in studies on single informants of the couple (Hardesty & Ogolsky, 2020;Marshall et al, 2021;Riesgo et al, 2019). Undoubtedly, the use of information from both partners allows a more refined analysis of relational patterns.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Collecting reports from both partners undoubtedly offers additional information in order to get more accurate explanations of IPV. Nevertheless, the limitation of the potential disagreement has been pointed out as a worrying issue in the study of dyads' responses (Marshall et al, 2021). For example, high levels of concordance have been attributed to a large number of nonviolent couples, inflating the general concordance levels and recent research has shown that eliminating these non-violent couples' concordance levels are low to moderate (Marshall et al, 2021;Riesgo et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Starting in the early 1980s, studies examining concordance using the Conflict Tactics Scale (CTS; Straus, 1979) have suggested that there are very low levels of agreement in reports of IPV in heterosexual couples (Szinovacz, 1983; Edleson & Brygger, 1986; Kuijpers, 2020; Marshall et al, 2020), and that women are more likely to report experiences of IPV in general (Marshall et al, 2020) including their own use of IPV (Kuijpers, 2020). Previous literature has also shown higher agreement between both partners in reports of female-to-male partner violence (FMPV) than those of male-to-female partner violence (MFPV) (LaMotte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%